Navigating Approaches to “Thinking With”: A Discussion of the Practicalities of Posthuman Research Involving Young Children - Elizabeth Y. S. Boileau (Australian Journal of Environmental Education)
Though there has been a marked increase in research driven by posthumanist theory and inspired by the common worlds research approach, practical approaches to conducting this type of research have not been well documented and shared within the literature. This article explores the process of navigating the planning and conducting of research that aims to think with more-than-human worlds. Three research methods that were applied in a study involving young children in a forest school program are described: (1) non-participant observation, (2) observing the park through “sit spots,” and (3) the use of wearable cameras to film a different perspective. I explore each of these as a way to guide other researchers grappling with the tensions and challenges of conducting posthumanist research. Any combination of these methods could be considered within research that aims to disrupt the dominant anthropocentric lens in early childhood education for sustainability and beyond.